The Things Things Say - Lamb, Jonathan (Princeton University Press, 2011)
One of the new forms of prose fiction that emerged in the eighteenth century was the first-person narrative told by things such as coins, coaches, clothes, animals, or insects. This is an ambitious new account of the context in which these "it narratives" became so popular. What does it mean when property declares independence of its owners and begins to move and speak? Jonathan Lamb addresses this and many other questions as he advances a new interpretation of these odd tales, from Defoe, Pope, Swift, Gay, and Sterne, to advertisements, still life paintings, and South Seas journals. Lamb emphasizes the subversive and even nonsensical quality of what things say; their interests are so radically different from ours that we either destroy or worship them. Existing outside systems of exchange and the priorities of civil society, things in fact advertise the dissident obscurity common to slave narratives all the way from Aesop and Phaedrus to Frederick Douglass and Primo Levi, a way of meaning only what is said, never saying what is meant. This is what Defoe's Roxana calls "the Sense of Things," and it is found in sounds, substances, and images rather than conventional signs. This major work illuminates not only "it narratives," but also eighteenth-century literature, the rise of the novel, and the genealogy of the slave narrative. -- Provided by publisher.
Description based upon print version of record.
Keywords: English literature -- 18th century -- History and criticism.; Personal belongings in literature.; Property in literature.; Littérature anglaise -- 18e siècle -- Histoire et critique.; Objets personnels dans la littérature.; English literature; Personal belongings in literature; Property in literature; 1700-1799; Aesop.; Arabian Nights.; Bacon, Francis.; Blunden, Edmund.; Brandeis, Louis.; Copyright Act.; Defoe, Daniel.; Deutsch, Helen.; Don Quixote (Cervantes).; Fantomina (Haywood).; Gallagher, Catherine.; Gildon, Charles.; Gothic novel.; Grub Street.; Hawkesworth, John.; Heidegger, Martin.; Hollar, Wenceslaus.; Hume, David.; Jünger, Ernst.; Kirkman, Francis.; Lennox, Charlotte.; Leviathan (Hobbes).; Locke, John.; Michelangelo.; Narcissus.; Navy Board.; Oedipus.; Quintilian.; Rambler.; advertisements.; authority.; camera obscura.; chapbook.; curiosities.; ekphrases.; entail.; fiction.; folk tales.; identity.; idolatry.; imagination.; it-narratives.; justice.; labor.; magic.; metempsychosis.; muru.; objects.; panpsychism.; passion.; probability.; realism.; Criticism, interpretation, etc.